Conocimiento y práctica de medidas preventivas sobre vih/sida en adolescentes del asentamiento humano Violeta Correa de Belaunde, Iquitos 2022 - Del Aguila Pinedo, Karen Xiomara (2024)
The objective of the study was to determine the relationship between knowledge and practice of preventive measures on HIV/AIDS in adolescents of both sexes from the Violeta Correa de Belaunde Human Settlement, Iquitos 2022. The type of research was the quantitative design, the non-experimental, the correlational and the transversal. The sample was 50 adolescents. The techniques were the interview and the home visit. The HIV/AIDS knowledge questionnaire was used, which had a validity of 98.2% and a reliability of 96.5%, and the HIV/AIDS preventive measures practices questionnaire with a validity of 83.0% and a reliability of 96.5%. 81.0%. The results were: in knowledge about HIV/AIDS, 68% achieved low knowledge, 20% average knowledge and 12% high knowledge; In the practices of preventive measures on HIV/AIDS, 88% had incorrect practices, while only 12% had correct practices. Using the Chi Square, statistical significance was found (p=0.000). Therefore, it is concluded that there is a relationship between knowledge and practice of preventive measures on HIV/AIDS in adolescents of both sexes from the Violeta Correa de Belaunde Human Settlement in Iquitos, 2022.